The status of elementary teacher education in Indonesia - Harahap, Amir Yahya (s.n.], 1969)
The study surveyed the only educational agency charged with the responsibility of producing and maintaining elementary teachers in Indonesia at present. This investigates the status of teacher education for elementary schools with respect to administration and curriculum. Documentary analysis has been used to pursue the study.